ANALYSIS OF FLOOD DISTRIBUTION IN SUB-WATERSHED BENDUNG BY USING GEOGRAPHIC INFORMATION SYSTEM (GIS) - Rully Marinto; Ngudiantoro Ngudiantoro; Ari Siswanto (Biota, 2018)
The research was conducted to map the level of flood vulnerability in the area around Sub DAS Bendung and Analyzing the influence of natural factors causing flood and land cover factors on flood vulnerability in the area around Sub DAS Bendung. In the rainy there are floods in some locations. The Flood of Sub DAS Bendung are influenced by several factors including natural factors such as river characteristics, which have small river channel capacity, some areas that are swamp, sea tides that resist the flow of river, and relatively flat topography conditions, so some Sub DAS Bendung area is a flood plain. Studies of the main causes of flooding in Palembang City or in other areas are very important. The use of GIS as an analytical tool will make it easier to examine the factors causing flooding to classify areas with high flood vulnerability. Thus expected to profide solutions and reduce the impacts caused by floods